PENGARUH INOVASI PRODUK KREATIF KASONGAN YOGYAKARTA MENEMBUS PASAR INTERNASIONAL - Wendri Rusli; Citra Ayudiati; Gita Apriliana (Journal Competency of Business, 2017)
This paper tries to investigate the role of art the creative process in the creative industry entrepreneurs using a qulitative approach. The sample were 34 entrepreneurs from taracotta industries. The investigation reveald that art were very helpful for the creative industry entrepreneurs to creation of new ideas. The skill in the art also has many advantages. The creative process consist of many stages and the role of enretion is very significant and sensitivity can be trained by education. The reference seeking important to sensitivity and internet is very important source in the process.